PENGARUH PEMBELAJARAN BERBASIS ETNOMATEMATIKA MELAYU RIAU TERHADAP HASIL BELAJAR SISWA KELAS IV SDN 08 KAMPUNG REMPAK - Almira Fatma Rizkayana; Zetra Hainul Putra; Eddy Noviana (STKIP Subang, 2026)
This research was motivated by students' lack of understanding in grasping the material presented by the teacher in mathematics lessons during the learning process. Therefore, the researcher conducted a study using another learning method to observe student development, namely ethnomathematics based on Riau Malay culture. This study aimed to determine the effect of the successful use of ethnomathematics based on Riau Malay culture on student learning outcomes. This study used a quasi-experimental method with a nonequivalent control group design. The results of this study showed an increase in learning outcomes, as evidenced by an increase in the average score of the experimental class from 50.75 to 70.25 and the control class from 47.78 to 60.28. The level of success of this Riau Malay ethnomathematics-based learning was very strong, with an effect size of 81.13%.